2022
DOI: 10.34133/2022/9753427
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Maturity of Greenhouse Grapes Based on Imaging Technology

Abstract: To predict grape maturity in solar greenhouses, a plant phenotype-monitoring platform (Phenofix, France) was used to obtain RGB images of grapes from expansion to maturity. Horizontal and longitudinal diameters, compactness, soluble solid content (SSC), titratable acid content, and the SSC/acid of grapes were measured and evaluated. The color values (R,G,B,H,S,and I) of the grape skin were determined and subjected to a back-propagation neural network algorithm (BPNN) to predict grape maturity. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“… \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}\begin{equation*} RMSE=\sqrt{\frac{\sum \limits_{i=1}^n{\left({O}_i-{S}_{\mathrm{i}}\right)}^2}{\mathrm{n}}} \end{equation*}\end{document} % \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}\begin{equation*} RRMSE=\frac{RMSE}{\overline{O}}\times 100 \end{equation*}\end{document} where O i is the observed values and S i is the simulated values. The smaller the RMSE and RRMSE, the more accurate the simulation [ 84 ]. In this study, model accuracy is considered excellent when RRMSE <10%; good if 10% ≤ RRMSE <20%; fair if 20% ≤ RRMSE <30%; and poor if RRMSE ≥30% [ 85 ].…”
Section: Methodsmentioning
confidence: 99%
“… \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}\begin{equation*} RMSE=\sqrt{\frac{\sum \limits_{i=1}^n{\left({O}_i-{S}_{\mathrm{i}}\right)}^2}{\mathrm{n}}} \end{equation*}\end{document} % \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}\begin{equation*} RRMSE=\frac{RMSE}{\overline{O}}\times 100 \end{equation*}\end{document} where O i is the observed values and S i is the simulated values. The smaller the RMSE and RRMSE, the more accurate the simulation [ 84 ]. In this study, model accuracy is considered excellent when RRMSE <10%; good if 10% ≤ RRMSE <20%; fair if 20% ≤ RRMSE <30%; and poor if RRMSE ≥30% [ 85 ].…”
Section: Methodsmentioning
confidence: 99%
“…Manual inspection, however, can be inconsistent, labor-intensive, and unscalable for largescale production. The integration of computer vision and artificial intelligence has unlocked exciting new possibilities for automated, non-destructive, and real-time assessment of horticultural produce quality [132]- [136]. As explored by Tan et al [133], deep convolutional neural networks demonstrated high accuracy (mean average precision of 95.52%) in classifying the maturity of tomatoes based on color features extracted from images.…”
Section: H Greenhouse Crop Quality Inspectionmentioning
confidence: 99%
“…Wei et al [136] developed a model using grape skin color analysis and a backpropagation neural network to predict the maturity of greenhouse-grown grapes, achieving up to 79.4% accuracy. A two-factor color model performed better than single-color predictors.…”
Section: H Greenhouse Crop Quality Inspectionmentioning
confidence: 99%
“…The results showed that BPNN could classify Drunk Incense Grapes with recognition accuracy as high as 79.3%. Muscat Hamburg Grapes were classified with 78.2% accuracy, and Xiang Yue with 79.4% [21].…”
Section: Related Workmentioning
confidence: 99%